Online-Offline Satisfaction Gaps among University Students: Cochran’s Q and McNemar Tests - Nurmala Fitri; Amsyaroh Aini Nasution; Nasywa Kayo Rasaki Endha; Naomi Varera Sinaga; Aisyah Amir Harahap; Alde Barent Napitupulu; Khairul Ali Hutasuhut (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2026)
The rapid expansion of online shopping has reshaped consumer behavior; however, offline shopping remains preferred under certain conditions. This study examines satisfaction dimension gaps between online and offline shopping among university students using a repeated binary measures design. Data were collected through a questionnaire containing eight satisfaction indicators measured on a dichotomous scale (yes/no) from 26 respondents. Cochran’s Q test was applied to assess whether satisfaction proportions differ across dimensions, followed by McNemar’s test as an exploratory post-hoc procedure to provide diagnostic insights into the largest dimension gaps. The findings reveal meaningful variation across satisfaction dimensions. Online shopping demonstrates stronger satisfaction in convenience and payment security, while offline shopping shows higher satisfaction in product trial experience and perceived product assurance. Nevertheless, offline shopping exhibits comparatively lower satisfaction in service-related dimensions, indicating a potential weakness in interpersonal service delivery. These results confirm that consumer satisfaction is multidimensional and that satisfaction gaps across shopping channels are not uniform. The study offers practical insights for businesses to formulate channel-specific strategies to improve service quality and customer experience in both online and offline retail environments.